Pursuing Chemical Efficiency by Using Supported Organocatalysts for Asymmetric Reactions under Aqueous Conditions - Guillena, Gabriela; Alonso, Diego; Baeza, Alejandro; Chinchilla, Rafael; Flores-Ferrandiz, Jesus; Gomez-Martinez, Melania; Trillo, Paz (Current Organocatalysis, 2015)
Over the past decade, a great effort has been made by the chemical community to improve the efficiency of organic transformations and allow sustainable processes. Merging the use of supported and recyclable organocatalysts and aqueous conditions for the asymmetric synthesis of valuable molecules, has led to outstanding contributions in the area of green chemistry. Recent progresses in the field include the implementation of these methodologies in the large scale production of chiral molecules using automated flow chemistry.
Keywords: organocatalysis